Tertiary treatment palm oil mill effluent using fenton oxidation - Aris, Azmi; Ooi, Boon Siew; Kon, Suh Kee; Ujang, Zaini (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2008)

(untitled)
A study was conducted to determine the feasibility of Fenton oxidation process in treating biologically treated palm oil mill effluent (BT-POME). Two types of Fenton processes were evaluated, namely ambient-Fenton and solar-Fenton. Both were conducted in batch mode at laboratory scale and the efficiency of the processes was assessed based on COD and color removal. The mechanism of removal in the solar-Fenton process was also explored. Both processes were found to be efficient in treating the wastewater. The highest removals of COD and color for ambient-Fenton were 75.2% and 92.4%, respectively. The COD and color removal of 82.4%, and 95.1%, respectively, were achieved by solar-Fenton. The solar-Fenton removal was mainly through oxidation process. Precipitation and coagulation of iron also contributed to the removal of COD and color but at a lesser extent. Enhancement of color removal by the coagulation process is mainly through elimination of the remaining iron rather than removal of the organics. The role of iron and hydrogen peroxide in ambient- and solar-Fenton was statistically evaluated and discussed